Development of a quantitation approach for total human and male DNA based on real time PCR followed by high resolution melting analysis. Issue 21 (7th September 2016) - Ginart, Santiago; Caputo, Mariela; Alechine, Evguenia; Corach, Daniel; Sala, Andrea
Abstract : We developed and validated a total human DNA quantitation technique that simultaneously allows male DNA detection. This assay, called Amel‐Y, is a duplex Real Time PCR followed by HRM (high resolution melting) analysis using the intercalating dye SYTO9. Amel‐Y duplex produces two amplicons, one for the amelogenin gene (106/112 bp, female/male) and another (84 bp) corresponding to human Y chromosome‐specific fragment to detect male DNA. After HRM analysis, two melting peaks differing in 5.3°C–5.5°C are detected if both male and female DNA are present and only one if only female DNA is present. For specificity assessment, the inclusion of high concentrations of bacterial and fungal DNA in the quantitation reactions allowed discarding species cross‐reactivity. A set of crime scene evidence from forensic casework has been quantified with commercial kits and compared with Amel‐Y duplex. Our method detected male DNA from a concentration of 18 pg/μL and supports autosomal/Y DNA detection ratio up to 200:1. A limitation of the technique is its inability to quantify male and female donnors in a mixed sample. The Amel‐Y duplex demonstrated to be an efficient system for quantifying total human DNA being a specific, rapid, sensitive, and cost‐effective method suitable for mixed DNA samples and applicable to any field where human DNA quantification is required, such as molecular diagnosis, population genetics, and forensic identification.